How Female Mice Attract Males: A Urinary Volatile Amine Activates a Trace Amine-Associated Receptor That Induces Male Sexual Interest - Harmeier, Anja; Meyer, Claas A.; Staempfli, Andreas; Casagrande, Fabio; Petrinovic, Marija M.; Zhang, Yan-Ping; Künnecke, Basil; Iglesias, Antonio; Höner, Oliver P.; Hoener, Marius C. (Frontiers in Pharmacology, 2018)
Individuals of many species rely on odors to communicate, find breeding partners, locate resources and sense dangers. In vertebrates, odorants are detected by chemosensory receptors of the olfactory system. One class of these receptors, the trace amine-associated receptors (TAARs), was recently suggested to mediate male sexual interest and mate choice. Here we tested this hypothesis in mice by generating a cluster deletion mouse (Taar2-9-/-) lacking all TAARs expressed in the olfactory epithelium, and evaluating transduction pathways from odorants to TAARs, neural activity and behaviors reflecting sexual interest. We found that a urinary volatile amine, isobutylamine (IBA), was a potent ligand for TAAR3 (but not TAAR1, 4, 5 and 6). When males were exposed to IBA, brain regions associated with sexual behaviors were less active in Taar2-9-/- than in wild type males. Accordingly, Taar2-9-/- males spent less time sniffing both the urine of females and pure IBA than wild type males. This is the first demonstration of a comprehensive transduction pathway linking odorants to TAARs and male sexual interest. Interestingly, the concentration of IBA in female urine varied across the estrus cycle with a peak during estrus. This variation in IBA concentration may represent a simple olfactory cue for males to recognize receptive females. Our results are consistent with the hypothesis that IBA and TAARs play an important role in the recognition of breeding partners and mate choice.